PENGARUH KEPERCAYAAN, KEMUDAHAN, KUALITAS PRODUK, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN SAYURAN SECARA ONLINE DI KOTA JAKARTA SELATAN - Bekti Noviana Ulfa; Siswanto Imam Santoso; Wahyu Dyah Prastiwi (Universitas Galuh, 2023)
The purpose of this study was to describe consumer characteristics and consumption behavior of buying vegetables online and analyzing the effect of trust, convenience, product quality, and price on online vegetable purchasing decisions in South Jakarta.The study was conducted in South Jakarta in June – July 2022. The population were the people of South Jakarta who knew about Sayurbox, Tanihub, or Happyfresh. The sampling method was a non-probability sampling with purposive sampling technique, respondents criteria in this study were women or men who are at least 18 years old, who actively working and domiciled in South Jakarta, and knew about Sayurbox, Happyfresh or Tanihub. The number of samples required were 100 respondents. This research was an explanatory research with questionnaire as a tool to collect the data. Data were analysed using binary logistic regression. The results showed that respondents in this study were dominated by women, the majority aged 21 – 23 years, worked as private employees, and had income levels between > Rp. 3,000,000 – Rp. 5,000,000. per month. The most frequently used e-commerce platform by respondents is Happyfresh, the majority of online vegetable purchases are 2-4 times a week, and the expenditure for online vegetable shopping is Rp. 250.001 – Rp. 350,000. per month.the and the variables of trust and convenience had no effect on purchasing decisions, while product quality and price variables had a significant effect on purchasing decisions.